P21 is not a prognostic marker for rectal cancer – five-year follow up study of rectal cancer in stages I–IV - Kozłowska-Geller, Monika A.; Głuszek, Stanisław Z.; Lewitowicz, Piotr (Contemporary Oncology/Współczesna Onkologia, 2020)
The p21 participates in the regulation of DNA repair and replication, and modulation of apoptosis as well. After DNA damage, the p53-dependent induction of p21 results in cell cycle arrest or could trigger cell apoptosis. The objective of the study was the assessment of p21 immunoreactivity in rectal cancer and the estimation of relationships with clinical outcome especially as predictor of poor outcome. While applying the ruling in and out criteria, 102 patients were incorporated to the study, with stage I–IV rectal cancer who had undergone surgery in a planned mode during 2005–2011. The follow-up covered 5 years period from surgery date. Conventional immunohistochemistry were performed using antibody against p21 (p21WAF1 (Clone H252) to detect overexpression targeted receptor. The analysis showed no statistically significant differences in the survival curves of patients in groups with immunoreactivity of p21 protein at 0; 1; 2; 3 (p = 0.6453 in the log-rank test), also is not a significant risk factor for death (HR = 0.915, p = 0.7842) and for tumor dissemination (HR = 0.94, p = 0.9426). Our study leads to the conclusion that the probability of survival does not depend on p21 expression and do not authorize the importance of p21 immunoreactivity in the detection and monitoring of rectal cancer treatment.